Endogenous ethanol- and thermo-tolerant strain from Malaysia pineapple peel: Screening and molecular characterisation - Selvanathan, Yashini K; Nor Hasmaliana, Abdul Manas; Norazwina, Zainol; Nasratun, Masngut (Elsevier, 2024)
The current study aims to identify an endogenous acetic acid bacterial strain isolated from a Malaysian pineapple capable of tolerating high ethanol and temperatures. A total of 23 strains of presumed acetic acid bacteria were isolated from the pineapple peel waste. Subsequently, three isolates with the highest acid yield were subjected to 16S rDNA sequencing; Acetobacter tropicalis (A. tropicalis), Staphylococcus haemolyticus, and Staphylococcus ureilyticus. Tolerance evaluations against pH, temperature, ethanol, sugar, and acetic acid demonstrated that all three strains tolerated significant temperatures, ethanol, and sugar levels. Based on the results, A. tropicalis possesses the potential to reduce cooling system load during acetic acid manufacture in hot climate regions with a notable acetic acid yield.